Pleading poverty (or identifying with the poor for selfish reasons) : on the ideology of Psalm 109 - Scheffler, Eben (Old Testament essays, 2011)
In this article the popular view that the "voice of the poor" is expressed in the Psalms (the so-called Armenfrömmigkeit) is challenged. Although the psalms contain many references in which a positive concern for the extremely poor are expressed, this is not always the case. Psalm 109 is discussed as an example in which the supplicant identifies with the poor for his own interest. It is argued that the reader of the psalms should not merely accept that all references to the poor in the psalms could (from a hermeneutical perspective) positively be appropriated. "Pleading poverty" to selfishly justify feelings of enmity should be exposed in the psalms - not only for honesty's sake, but also for the sake of the really poor.